2011
DOI: 10.1111/j.1365-3180.2011.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for biological control of Ambrosia artemisiifolia in Europe: learning from the past

Abstract: SummaryThe recent invasion by Ambrosia artemisiifolia (common ragweed) has, like no other plant, raised the awareness of invasive plants in Europe. The main concerns regarding this plant are that it produces a large amount of highly allergenic pollen that causes high rates of sensitisation among humans, but also A. artemisiifolia is increasingly becoming a major weed in agriculture. Recently, chemical and mechanical control methods have been developed and partially implemented in Europe, but sustainable contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 49 publications
(95 reference statements)
1
109
0
4
Order By: Relevance
“…Cannabis on ruderal habitats and agricultural land, and Urtica/Parietaria on ruderal habitats); (2) All host-range tests conducted so far indicate that O. communa is specific to the Asteraceae tribe Heliantheae (Palmer and Goeden 1991;Gerber et al 2011). As a result, Cannabaceae and Urticaceae populations could be affected by Ambrosia eradication measures in the Milan area, and concurrent decreases in airborne Cannabaceae and Urticaceae pollen are unlikely to be caused by beetle attacks.…”
Section: Airborne Pollen Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabis on ruderal habitats and agricultural land, and Urtica/Parietaria on ruderal habitats); (2) All host-range tests conducted so far indicate that O. communa is specific to the Asteraceae tribe Heliantheae (Palmer and Goeden 1991;Gerber et al 2011). As a result, Cannabaceae and Urticaceae populations could be affected by Ambrosia eradication measures in the Milan area, and concurrent decreases in airborne Cannabaceae and Urticaceae pollen are unlikely to be caused by beetle attacks.…”
Section: Airborne Pollen Datamentioning
confidence: 99%
“…The flight distance has been estimated to be approximately 25 km/day, with potential range expansion of 329 km/year (Yamamura et al 2007;Tanaka and Yamanaka 2009). Taking into account the selective host-feeding preferences, high fecundity and dispersal potential, it is suggested that O. communa may be a potential biological control agent against A. artemisiifolia (Teshler et al 2002) although Ophraella slobodkini was a preferred candidate species for the biological control of A. artemisiifolia in Europe, because it exclusively feeds on Ambrosia (Gerber et al 2011).…”
mentioning
confidence: 99%
“…Since the 1960s, biological control had been considered as a management option against common ragweed in different parts of the world, including non-EU Member States in Europe (Gerber et al 2011). The noctuid moth Tarachidia candefacta (Hübner) (Lepidoptera: Noctuidae), which was released in Russia in 1969, was the first such intentional attempt to control common ragweed by biological means (Kovalev 1971), but so far with little impact.…”
Section: Ambrosia Artemisiifolia L (Common Ragweed) (Asteraceae)mentioning
confidence: 99%
“…Emphasis was put on biological control by promoting and coordinating studies on the host-specificity and impact of selected insect and fungal BCAs (Gerber et al 2011). In 2013, biological control efforts against common ragweed experienced an unexpected boost when the North American leaf beetle Ophraella communa LeSage (Coleoptera: Chrysomelidae) was detected in Northern Italy and Southern Switzerland Müller-Schärer et al 2014).…”
Section: Ambrosia Artemisiifolia L (Common Ragweed) (Asteraceae)mentioning
confidence: 99%
“…Given its potential impact on common ragweed, O. communa had already been mentioned as the most promising candidate BC agent for Europe by Kiss (2007). It was, however, not regarded as a candidate by Gerber et al (2011) for Europe and had earlier been rejected as a candidate for Australia because of its wider fundamental host range including sunfl ower (Palmer & Goeden, 1991). Feeding on sunfl ower and a few other plant species from the same tribe (Heliantheae) has indeed been reported based on results from no-choice tests in the laboratory (Palmer & Goeden, 1991;Cao et al, 2011), and from fi eld surveys after its accidental introduction into Japan (Yamazaki et al, 2000).…”
Section: Introductionmentioning
confidence: 99%